Examining the Significance of Social Class in the Effectiveness of Celebrity Endorsed Cosmetic Advertisements - Forster, Emily (2009)

(untitled)
Celebrity endorsements have become the most used and prevailing marketing strategy of advertising today in the UK. The ever-increasing public interest and fascination with celebrities provides marketers with the vast potential to promote their brands and expand their markets by capitalising on this phenomenon. Social class is conceptually complicated and methodologically challenging and yet continues to provide provoking insights into consumption choices.